2011
DOI: 10.1002/ccd.22915
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of single‐ versus two‐stent techniques in treatment of unprotected left main coronary bifurcation disease

Abstract: Compared with the two-stent technique, the single-stent technique showed more favorable long-term clinical outcomes in patients with distal unprotected LMCA disease who received DES

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
50
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 64 publications
(57 reference statements)
1
50
2
Order By: Relevance
“…As it was proved earlier PTS strategy ensures the best angiographic and clinical outcomes in a majority of studies [14]. Moreover, Kim et al [7] as well as others showed that one-stent technique is better than 2-stent technique [15]. There was a relatively low rate of stent implantation in SB (16.7% of cases).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…As it was proved earlier PTS strategy ensures the best angiographic and clinical outcomes in a majority of studies [14]. Moreover, Kim et al [7] as well as others showed that one-stent technique is better than 2-stent technique [15]. There was a relatively low rate of stent implantation in SB (16.7% of cases).…”
Section: Discussionmentioning
confidence: 88%
“…In general, based on non-randomized studies and extrapolations from the results of non-LM bifurcation trials, the provisional 1-stent approach has been considered a preferred strategy over the elective 2-stent technique for patients with LM bifurcation disease. In practice, however, 2-stent techniques are chosen more frequently for LM bifurcation than for non-LM lesions due to concerns regarding the ischemic myocardial volume, which would be jeopardized by adverse events [7].…”
Section: Introductionmentioning
confidence: 99%
“…We performed T-stenting with two everolimus-eluting stents. Although single stent technique showed more favorable long-term outcomes than two stents technique in treatment of LM disease [13], single stent technique is difficult, when there is a severe stenosis at the ostium of side brunch. As the stenosis at the ostium of LCX was very tight in our case, we adopted two stents technique.…”
Section: Discussionmentioning
confidence: 97%
“…More aggressive statin therapy in CAD patients with high CRP levels is associated with a better clinical outcome [15,16] , and therefore the index case was put on atorvastatin 40 mg/d throughout his follow-up course. The single stent technique as performed in the index case for the left main coronary artery bifurcation lesion has shown more favorable long-term clinical outcomes in comparison with the two-stent technique [17] . Risk factors such as diabetes, raised creatinine of >1.5 mg/dL, anemia, congestive heart failure and left ventricular dysfunction, present in the index case, are associated with contrast-induced nephropathy and adverse clinical outcomes following contrast load [18] .…”
Section: Discussionmentioning
confidence: 99%